2004
DOI: 10.1128/aac.48.2.392-395.2004
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Broad-Spectrum Cephalosporins by Piperacillin-Tazobactam: Impact on Sustained High Rates of Bacterial Resistance

Abstract: We have previously observed a significant reduction of ceftriaxone resistance in Proteus mirabilis associated with an increase in the use of cefepime, along with a decrease in the consumption of broad-spectrum cephalosporins (CEP). However, we did not observe such a reduction with Klebsiella pneumoniae. Therefore, we sought to determine whether replacement of CEP by piperacillin-tazobactam might be useful in reducing sustained high rates of CEP resistance by this organism. We used a 6-month "before and after m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 17 publications
1
33
2
2
Order By: Relevance
“…Switching from a broad range of agents to a restricted list as advised by the EAU guidelines resulted in a significant decrease in the proportion of pathogens subsequently causing postoperative infection that were resistant to these antibiotics. Avoidance of cephalosporins, for example, is likely to reduce the risk of development of extended betalactamase activity among uropathogenic Enterobacteriaceae, as reported by several authors [26]. Similarly, our observation that reduced overall use of gentamicin led to a lower risk of subsequent resistance among uropathogens echoes the findings of Kosmidis et al [27], who demonstrated that after a change in aminoglycoside use, gentamicin resistance rates decreased from 14.5% to 8.8%, whereas rates of resistance to other aminoglycosides remained unchanged.…”
Section: 3mentioning
confidence: 85%
“…Switching from a broad range of agents to a restricted list as advised by the EAU guidelines resulted in a significant decrease in the proportion of pathogens subsequently causing postoperative infection that were resistant to these antibiotics. Avoidance of cephalosporins, for example, is likely to reduce the risk of development of extended betalactamase activity among uropathogenic Enterobacteriaceae, as reported by several authors [26]. Similarly, our observation that reduced overall use of gentamicin led to a lower risk of subsequent resistance among uropathogens echoes the findings of Kosmidis et al [27], who demonstrated that after a change in aminoglycoside use, gentamicin resistance rates decreased from 14.5% to 8.8%, whereas rates of resistance to other aminoglycosides remained unchanged.…”
Section: 3mentioning
confidence: 85%
“…This intervention proved to be useful in reducing the resistance rates to CEPs of endemic nosocomial bacteria, especially K. pneumoniae, and was also effective in decreasing the incidence of ESBL-producing strains, particularly those belonging to Klebsiella spp. [5,14,23].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have suggested that a major risk factor for selection of ESBLproducing Enterobacteriaceae is increased consumption of third-and fourth-generation cephalosporins (CEPs), carbapenems and quinolones [11,12]. In this respect, formulary intervention through the reduction of broad-spectrum CEP usage and replacement by ␤-lactam/␤-lactamase inhibitor combinations as first-line empirical therapy have been shown to result in a decrease in the isolation rate of ESBL-producing Enterobacteriaceae [5,13,14]. 0924 The objective of the present study was to investigate whether, in a tertiary care hospital with significant problems of antimicrobial resistance, a formulary intervention through restriction of third-and fourth-generation CEPs, carbapenems and quinolones and replacement by piperacillin/tazobactam (TZP) as first-line empirical therapy may result in a decrease in the overall ␤-lactam resistance, and particularly in the rate of isolation of ESBL-producing Klebsiella pneumoniae and Escherichia coli isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Aunque existen múltiples formas de abordar el control de la resistencia bacteriana y el uso apropiado de antibióticos (24,25), la caracterización de la infección con base en la ecología bacteriana, los patrones de resistencia y las infecciones más prevalentes permite crear estrategias específicas de control epidemiológico que garan ticen una reducción del uso inapropiado de antibióticos y la resistencia bacteriana (15).…”
Section: Discussionunclassified